FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT BERWIRAUSAHA MAHASISWA MENGGUNAKAN THEORY OF PLANNED BEHAVIOR (Studi pada Mahasiswa Pelaku Wirausaha Fakultas Ekonomika dan Bisnis Universitas Diponegoro) - Sukmaningrum, Swastinitya; Rahardjo, Mudji (Faculty of Economics and Business Diponegoro University, 2017)
This research aims to examines the factors that effect the entrepreneurial intention of the students in the Faculty of Economics and Business in Diponegoro University. Related to the vision, mission and the objectives of the Faculty of Economics and Business in Diponegoro University, i.e. develop an academic community life which has the entrepreneurial soul on entire campus residents supported by scientific culture of faith and pious to Almighty God.The population in this research is the students in eight semester of the Faculty of Economics and Business in Diponegoro University. The sampling technique which used is proportional stratified sampling with the total sample 69 students. The analysis tool which used is multiple linear regression thus has tested the validity and reliability first. The analysis is used to examines the influence of self-efficacy, subjective norms, need for achievement, and parental background on the intention of entrepreneurship.The results shows that the self-efficacy, subjective norms, need for achievement, and parental background on the intention of entrepreneurship, are the influential factors that have a positive effect either partially or simultaneously. While the need for achievement is a factor that has the most impact in comparison with other factors. Another factor affecting student’s entrepreneurial intention is a subjective norm. Thus, the individuals who want to be an entrepreneurs, make sure that they will be supported by the surrounding people (family, close friends, and other important people) and can accept the suggestions and criticism from others to be better than the other.